Balance of Payments Constrained Economic Growth in the Baltics - Hansen, Jorgen Drud; Kvedaras, Virmantas (Ekonomika, 2004)
This paper examines, the prospects for economic growth in the three Baltic countries in a framework of a balance of payment constrained growth model. Based on an estimation of income elasticities of imports and assumptions about export growth, GDP growth rates are calculated consistent with balance of payment equilibrium or alternatively, consistent with a given growth rate of capital imports. The results show that the calculated rates of growth for Estonia and Lithuania are lower than the growth rates predicted from traditional supply side oriented growth models.